The role of Piri Reis and Ahmad Ibn Majid in developing the science of maritime navigation and drawing of geographical maps in the 16th century. - DJEBRI , Amar (La Revue d’Histoire Méditerranéenne, 2024)
This article aims to reveal the reasons for the superiority of the Ottoman and Omani navies in the 16th century, thanks to the expertise of maritime navigators such as Piri Reis and Ahmad ibn Majid. This study aims to highlight the reasons for the development of Arab and Islamic navigation in the 16th century. In this study, we have relied on a narrative and descriptive historical approach to the events, within a specific temporal and spatial framework that encompasses the waters of the Mediterranean Sea, the Indian Ocean, and the Arabian Gulf during the sixteenth century. We have also reached several conclusions, the most important of which are: The advancement of Arab and Muslims by The Ottoman navigation through the use of various advanced technical means, such as the astrolabe, the movable rudder, and the compass, alongside their reliance on navigational and geographical mapping. We also found that the Omani navigator Ahmad Ibn Majid contributed to the advancement of maritime navigation in the waters of the Indian Ocean and the Arabian Gulf through his diverse scientific writings on maritime navigation and the measuring and observational instruments he used to determine the direction of ships and geographical north.